A estrutura da narrativa em Visão do Paraíso de Sérgio Buarque de Holanda - Assis, Gabriella Lima de (2012)
This dissertation examines the writing of Sérgio Buarque de Holanda in Visão do Paraíso on the assumption that the historical narrative using literary devices to form a "print explanatory" in the sense proposed by Hayden White. First, this work presents the debate over the frontiers between history and literature, points out that current epistemological debate and examines the role of narrative in the production of historical knowledge. Secondly, the discussions go through the Brazilian historiography and highlights the place of production established by Sergio Buarque de Holanda. Finally, the analysis of Visão do Paraíso is developed in order to demonstrate the historical consciousness of its author, as well as their strategies of argumentation.